The Fracture Risk Assessment Tool (FRAX® score) in subclinical hyperthyroidism - Polovina, Snežana; Micić, Dragan; Miljić, Dragana; Milić, Nataša; Micić, Dušan; Popović, Vera (Vojnosanitetski pregled, 2015)
Background/Aim. The Fracture Risk Assessment Tool (FRAX® score) is the 10-year estimated risk calculation tool for bone fracture that includes clinical data and hip bone mineral density measured by dual-energy x-ray absorptiometry (DXA). The aim of this cross-sectional study was to elucidate the ability of the FRAX® score in discriminating between bone fracture positive and negative pre- and postmenopausal women with subclinical hyperthyroidism. Methods. The bone mineral density (by DXA), thyroid stimulating hormone (TSH) level, free thyroxine (fT4) level, thyroid peroxidase antibodies (TPOAb) titre, osteocalcin and beta-cross-laps were measured in 27 pre- and postmenopausal women with newly discovered subclinical hyperthyroidism [age 58.85 ± 7.83 years, body mass index (BMI) 27.89 ± 3.46 kg/m2, menopause onset in 46.88 ± 10.21 years] and 51 matched euthyroid controls (age 59.69 ± 5.72 years, BMI 27.68 ± 4.66 kg/m2, menopause onset in 48.53 ± 4.58 years). The etiology of subclinical hyperthyroisims was autoimmune thyroid disease or toxic goiter. FRAX® score calculation was performed in both groups. Results. In the group with subclinical hyperthyroidism the main FRAX® score was significantly higher than in the controls (6.50 ± 1.58 vs 4.35 ± 1.56 respectively; p = 0.015). The FRAX® score for hip was also higher in the evaluated group than in the controls (1.33 ± 3.92 vs 0.50 ± 0.46 respectively; p = 0.022). There was no correlations between low TSH and fracture risk (p > 0.05). The ability of the FRAX® score in discriminating between bone fracture positive and negative pre- and postmenopausal female subjects (p < 0.001) is presented by the area under the curve (AUC) plotted via ROC analysis. The determined FRAX score cut-off value by this analysis was 6%, with estimated sensitivity and specificity of 95% and 75.9%, respectively. Conclusion. Pre- and postmenopausal women with subclinical hyperthyroidism have higher FRAX® scores and thus greater risk for low-trauma hip fracture than euthyroid premenopausal women. Our results point to the use of FRAX® calculator in monitoring pre- and postmenopausal women with subclinical hyperthyroidism to detect subjects with high fracture risk in order to prevent further fractures.